The Quest to Bring Land under Social and Political Control: Land Reform Struggles of the Past and Present in Ecuador - Goodwin, Geoff (Journal of Agrarian Change, 2017)
Land reform was one of the most important policies introduced in Latin America in the twentieth century and remains high on the political agenda due to sustained pressure from rural social movements. Improving our understanding of the issue therefore remains a pressing concern. This paper responds to this need by proposing a new theoretical framework to explore land reform and providing a fresh analysis of historical and contemporary land struggles in Ecuador. Drawing on the pioneering work of Karl Polanyi, the paper characterizes these struggles as the attempt to increase the social and political control of land in the face of mounting commodification. The movement started in the 1960s and remains evident in Ecuador today. Exploring land reform in Ecuador from this theoretical perspective provides new insight into land struggles in the country and contributes to debates over land reforms of the past and present elsewhere in the Global South.
Political Sciences; Development Studies
Keywords: Ecuador; commodification; land markets; land reform; reforms; social movements

Urban Governance in Africa Today: Reframing, Experiences, and Lessons - Obeng-Odoom, Franklin (Growth & Change, 2017)
Progress in analysing the instrumental view of governance as an engine for growth, poverty reduction, and inclusive development has been held back by the difficulty in framing governance. This essay seeks to address this problem by 1) reframing urban governance 2) evaluating its aims, processes, and outcomes, and 3) explaining those outcomes on the basis of which some lessons are teased out. Using examples from Africa and an institutional political economy approach (based on institutional economics, Marxist political economics, Georgist political economics, and Polanyian political economy), I show that, overall, while urban economies are growing; both urban poverty and inequality levels have risen substantially. Urban governance has paved the way for new forms of urban development that only benefit the few. Not only are there differences in how urban services and resources are experienced, accessed, and controlled but the varieties are also socially differentiated. I argue that the underlying reasons for this disjuncture between 'urban governance' in theory and 'actually existing urban governance' are 1) difficulties in implementing urban governance theory consistently in practice, 2) problems arising because urban governance theory has been implemented in practice, 3) tensions that would entangle most policies which do not address historical and structural economic issues, 4) restrictive assumptions, and 5) incoherence among the different dimensions of urban governance. To resolve these contradictions, I put the case for major structural and institutional change involving: 1) the re-ordering of the roles of the state, market, and society as institutions of change; 2) re-working the relationships that bind together land, labour, capital, and the state, and 3) re-organising the channels for keeping the attainment of the ends of urban governance in check.
Development Studies
Keywords: Africa; economic development; economic policy; labor; labour; poverty reduction; public administration

State–peasant movement relations and the politics of food sovereignty in Mexico and Ecuador - Henderson, Thomas Paul (Journal of Peasant Studies, 2017)
This contribution argues that the articulation between the state and peasant organizations’ internal structures – the class characteristics of their mass bases, their leaderships and the modes of interaction between the two – is critical for determining the nature of contemporary struggles guided by the discourse of food sovereignty. It will show that that counter-hegemonic demands are not synonymous with counter-hegemonic practice; rather than struggling to replace the neoliberal food regime, many peasant organizations employ the food sovereignty discourse as a political tool in their negotiations with the state in order to access resources from within the prevailing neoliberal model, not to transform it.
Development Studies
Keywords: GRAMSCI; Antonio; 1891-1937; Via Campesina; agriculture & state - Ecuador; agriculture & state - Mexico; food regime; food sovereignty; hegemony; peasant organizations; peasant studies